Infrarenal high intra-abdominal testis: fusion of T2-weighted and diffusion-weighted magnetic resonance images and pathological findings - Seiji Hoshi (BMC Urology, 2017)
Abstract Background Several recent reports have demonstrated that the preoperative sensitivity and accuracy of identifying and locating non-palpable testes increases with the use of conventional MRI, in addition to diffusion-weighted imaging (DWI). Therefore, pre-operative prediction of the presence and location of testes using imaging techniques may guide management of intra-abdominal testis. Fowler-Stephens orchiopexy is effective for treating patients with intra-abdominal testis; however, long-term testicular function after this procedure has not been clarified. We present a case of a high intra-abdominal testis located below the kidney, and discuss the usefulness of fusion view with T2-weighted and DWI images to make a diagnosis of high intra-abdominal testis and the pathological findings to predict future fertility potential. Case presentation A 10-month-old boy was referred to the urology department for the management of non-palpable testis. We employed not only conventional MRI, but also DWI, to improve the diagnostic accuracy of non-palpable testes by MRI examination. The high-intensity mass-like structure below the kidney on the T2-weighted image and the markedly high signal intensity mass on the DWI image completely matched, which suggested that the mass below the kidney was the right testis. The patient underwent diagnostic and therapeutic laparoscopy. A testis was found under the ascending colon, 1 cm below the right kidney. We performed 2-stage Fowler-Stephens orchiopexy. The testis could be delivered to the scrotum without any tension. We examined expression patterns of the stem cell marker, undifferentiated embryonic cell transcription factor 1 (UTF1) in the testicular biopsy sample, and demonstrated that the UTF1-positive Ad spermatogonia / negative Ad spermatogonia ratio was lower in this patient than in boys his age with descended and inguinal undescended testes, indicating that spermatogonial stem cell activity may decrease remarkably in this boy. Conclusions Fusion view with T2-weighted and DWI images may be a useful diagnostic modality for high intra-abdominal testes. Fowler-Stephens orchiopexy may provide blood supply to the testis but that might not be enough to achieve spermatogenesis.